A New Fingerprint Definition For Effective Song Recognition - Salvatore Serrano; Murtadha Arif Sahbudin; Chakib Chaouch; Marco Scarpa (Elsevier B.V., 2024)
Pattern Recognition Letters Volume 160, August 2022, Pages 135-141